Systematic analysis and case series of the diagnosis and management of trichilemmal carcinoma - Sun, Jiachen; Zhang, Lihua; Xiao, Minglu; Li, Shiyi; Chen, Runkai; Li, Ying; Yang, Yuguang (Frontiers in Oncology, 2023)
Background Trichilemmal carcinoma (TLC) is a rare malignant cutaneous adnexal neoplasm, with no relatively comprehensive research. Objective To perform an updated statistical analysis, so as to better understand TLC’s epidemiology, clinical features, diagnosis and treatment. Methods The diagnosis and treatment of 3 TLC cases in our department were summarized. Then, all TLC cases published in the literature were retrieved for a comprehensive analysis, followed by the analysis of global trends and regional distribution, demographic characteristics, clinical features, pathogenesis, histopathological features, and treatment and prognosis of TLC. Results Of the 231 cases, the incidence of TLC has shown an upward trend recently, especially in Asia, China. The susceptible population is males aged 60-80 and females over 80, and the most prone location is head and neck. The phenotype of TLC is not always typical, may be misdiagnosed due to the coexistence of other diseases. There is a linear relationship between the diameter and its duration or thickness. UV, locally present skin lesions, trauma, scarring, organ transplantation and genetic disorders may trigger the occurrence of TLC. PAS staining and CD34 but not EMA were helpful in the diagnosis of TLC. Though effective, surgical excision and MMS need further improvement to reduce recurrence of TLC. Carcinoma history is an independent risk factor for TLC recurrence. Limitations Lack of randomized controlled trial on TLC treatment and recurrence. Conclusion TLC has the possibility of invasive growth and recurrence, especially in patients with longer duration and carcinoma history.